Differential Analysis of Early-Onset and Late-Onset Colorectal Cancer Based on Multidimensional Evidence Integration: A Review - Xiaoying Mi MS; Peng Zheng MS; Xiangbai Wu MS (Cancer Control)
With the introduction of early-onset colorectal cancer (EO-CRC), defined as diagnosis before the age of 50, research has increasingly focused on distinguishing it from late-onset colorectal cancer (LO-CRC). However, the majority of these studies have delved deeply into specific aspects of the condition, and there is still a limited number of articles that comprehensively review the overall differences between EO-CRC and LO-CRC. In this review, we conducted literature searches on PubMed, Embase, and ScienceDirect databases using keywords such as “early-onset colorectal cancer”, and “late-onset colorectal cancer”. The retrieved articles were further screened to select those related to clinical manifestations, pathological features, molecular mechanisms, and prognosis for detailed analysis. Our findings indicate that the potential pathogenesis of EO-CRC is closely associated with lifestyle and environmental changes of the younger population. Compared to LO-CRC, EO-CRC tends to present with more severe initial symptoms, is more often diagnosed at an advanced stage, and primarily affects the left half of the colon. Postoperative pathology shows greater malignancy and invasiveness. At the biomolecular level, PIK3CA mutation and TP53 deletion exhibits a higher mutation rate in EO-CRC compared to LO-CRC, while other common gene mutations such as APC, KRAS, and SMAD4 are relatively less frequent. Additionally, MSI-H is more prevalent in patients with EO-CRC. Differences in transcriptomics and metabolomics profiles have also been observed between EO-CRC and LO-CRC, which may account for their distinct biological characteristics. The prognosis of EO-CRC is a subject of controversy, with varying trends observed across different age groups at onset, as well as between genders and ethnicities. In this study, we aimed to uncover the potential mechanisms behind the continuous rise in EO-CRC incidence and to provide a basis for optimizing standardized screening and treatment strategies for EO-CRC through a comprehensive analysis of the differences between EO-CRC and LO-CRC.